2015
DOI: 10.3923/ijv.2015.77.86
|View full text |Cite
|
Sign up to set email alerts
|

Partial Nucleotide Sequence of the Family Bunyaviridae Associated with a Mosaic-Diseased Fig. in North Egypt

Abstract: Four different patterns of chlorotic blotches, mosaic, yellowish mottling and deformation were observed and collected in four fig-growing areas of North Egypt from cv. Sultany farms. Fig mosaic virus like symptoms were successful purified through transmission an eriophyid mite, Aceria ficus Cotte to healthy potted rooted cuttings grown under glasshouse conditions. Young leaves appearing typical symptoms caused by FMV. Electron microscope observations of thin-sectioned tissues from symptomatic leaves showed Dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…On the other hand, Ref. [ 3 ] stated that sequence and phylogenetic analysis revealed that the Egyptian FMV isolate was closely related to other FMV isolates, particularly the Italian and Arkansas isolates with 80% similarity; however, Ref. [ 2 ] reported that nucleotide analyses of the two viruses studied (FMV and FLMaV-2) revealed that the sequence of FMV amplicons generated from different infected plants had 100% identity between the two isolates and showed 86.8–90.2% identity with other isolates reported in the GenBank database for FMV strains, whereas the two FLMaV-2 strains were 92.2% identical and showed 86.8–94.4% identity with other strains reported in the GenBank database.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Ref. [ 3 ] stated that sequence and phylogenetic analysis revealed that the Egyptian FMV isolate was closely related to other FMV isolates, particularly the Italian and Arkansas isolates with 80% similarity; however, Ref. [ 2 ] reported that nucleotide analyses of the two viruses studied (FMV and FLMaV-2) revealed that the sequence of FMV amplicons generated from different infected plants had 100% identity between the two isolates and showed 86.8–90.2% identity with other isolates reported in the GenBank database for FMV strains, whereas the two FLMaV-2 strains were 92.2% identical and showed 86.8–94.4% identity with other strains reported in the GenBank database.…”
Section: Discussionmentioning
confidence: 99%
“…The common fig ( Ficus carica L., Moraceae ) was one of the first cultivated fruit crops in the Mediterranean region, which is now regarded as the world's leading fig-producing region [ 1 , 2 ], and it is very important in Egypt [ 3 ]. Fig fruits may be eaten fresh or dried and are known for their moderate laxative properties [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%